0338 Insomnia in Late Pregnancy: Characterizing Phenotypes and Identifying Associated Factors. (12th April 2019) - Cuamatzi-Castelan, Andrea S; Kalmbach, David A; Atkinson, Rachel; Sangha, Roopina; Bazan, Luisa; O'Brien, Louise M; Swanson, Leslie M; Roth, Thomas; Drake, Christopher L
Abstract: Introduction: Insomnia increases across the prenatal period. This study characterizes insomnia phenotypes in late pregnancy, and identifies factors related to prenatal insomnia. Methods: A cross-sectional analysis of pregnant women (29.6±4.7 years, gestational weeks 26-33) receiving prenatal OB care at a large Midwestern health system completed online surveys on sleep and pregnancy-related factors. Results: Over half of the sample screened positive for clinical insomnia (n=97/163; 59.5%). Pregnant women with insomnia reported sleeping a nightly average of 6 hrs and 8 minutes (±1.20 hrs) compared to 7 hrs and 26 minutes (±1.11 hrs) for their good-sleeping counterparts (t=-6.99, p<.001). Nearly half of pregnant women with insomnia (40.2%) take medication for their sleep problems. Among insomniacs, difficulty staying asleep was the most common insomnia complaint (88.7%), although trouble falling asleep was also highly prevalent (40.2%). Factors associated with insomnia included greater discomfort during sleep (t=7.54, p<.001), having a high-risk pregnancy (t=2.66, p<.01), and low income (t=-3.10, p<.01). Snoring, history of miscarriage, and having a planned pregnancy were not related to insomnia symptoms. Conclusion: Insomnia is endemic to women in late pregnancy, many of whom are using sleep aids. Having a high-risk pregnancy, low household income, and discomfort during sleep potentially contribute to prenatal insomnia. Given that insomnia increases across pregnancy, it is important to regularly assess for insomnia in routine prenatal care. This will allow for identification of women early in the disease process. Early non-pharmacologic intervention carries potential to safely improve mother and infant outcomes and curb the use of sleep aids. Support (If Any): N/A